Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004370.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin for presumed viral myocarditis in children and adults

Abstract: Evidence from one trial does not support the use of IVIG for the management of adults with presumed viral myocarditis. There are no randomized paediatric trials. Further studies of the pathophysiology of this entity would lead to improved diagnostic criteria which would facilitate future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 32 publications
1
38
0
3
Order By: Relevance
“…We used steroids and immunoglobulin to treat the myocarditis. While immunoglobulin use has been reported to have no effect on mortality (19,20), a recent randomized study (21) suggested that steroid therapy significantly improves cardiac function in patients with viral myocarditis. It is difficult to determine the efficacy of steroid therapy for Legionellaassociated myocarditis because there are other confounding factors besides steroid therapy; however, it might provide some beneficial impact on the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We used steroids and immunoglobulin to treat the myocarditis. While immunoglobulin use has been reported to have no effect on mortality (19,20), a recent randomized study (21) suggested that steroid therapy significantly improves cardiac function in patients with viral myocarditis. It is difficult to determine the efficacy of steroid therapy for Legionellaassociated myocarditis because there are other confounding factors besides steroid therapy; however, it might provide some beneficial impact on the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 A Cochrane review concluded that IVIG should not been given routinely in any cases of pediatric or adult patients with presumed viral myocarditis. 17 Likewise, the effectiveness of steroids in children with myocarditis had not been confirmed. 18 There is insufficient evidence to support the routine use of immunosuppressive therapy in pediatric myocarditis, except for giant cell and eosinophilic myocarditis.…”
Section: Treatmentmentioning
confidence: 99%
“…Further studies to investigate independent and possibly yet unknown or unidentified influences in suicide are necessary [47][48][49][50][51][52].…”
Section: Limitations Of This Study Include the Followingmentioning
confidence: 99%